Context-Aware Mobile Collaborative Systems: Conceptual Modeling and Case Study - Luis G. Montané-Jiménez; Carmen Mezura-Godoy; Edgard Benítez-Guerrero (Sensors, 2012)
A Mobile Collaborative System (MCOS) enable the cooperation of the members of a team to achieve a common goal by using a combination of mobile and fixed technologies. MCOS can be enhanced if the context of the group of users is considered in the execution of activities. This paper proposes a novel model for Context-Aware Mobile COllaborative Systems (CAMCOS) and a functional architecture based on that model. In order to validate both the model and the architecture, a prototype system in the tourism domain was implemented and evaluated.